Malignant Glomus Tumour: A Case Report and Review of the Literature. (2003) - De Chiara, Annarosaria; Apice, Gaetano; Mori, Stefano; Silvestro, Giustino; Losito, Simona N.; Botti, Gerardo; Ninfo, Vito
Abstract : Purpose: Glomus tumours are characteristically benign solitary tumours. At our knowledge, about 23 reports are present in literature regarding the malignant counterpart, but only a minority developed metastases. We describe a locally aggressive glomus tumour with lymphnode metastasis. Patient: The patient was a 40 year-old man presenting a 1.5-cm lesion on the right wrist incompletely excised and a recurrent tumour, 4 × 2 cm in size, removed after 9 months, for which he received radiotherapy. After 2 years he developed an axillary lymphnode metastasis. Results: Histologically, both tumours (primary and metastasis) were similar. There were sheets and nests of uniform small cells with scant eosinophilic cytoplasm and round to polygonal nuclei; there was some degree of pleomorphism and the mitotic index was high (up to 18 m/10 HPF). The tumour cells were positive for vimentin and smooth muscle actin, but negative for desmin, NSE, Factor VIII, chromogranin, cytokeratin. Remarkably, in the primary, the cells strongly expressed p53 (70%) and MIB-1 (35%). Discussions: In many reported malignant cases, the histology of the tumour cells suggested that they were malignant, yet the clinical course has been benign. Carefully reviewing the literature, it seems that actually we have enough histological criteria to identify the cases with biological adverse outcome. Those unfortunate cases behave as high grade sarcomas and therefore may deserve an aggressive therapeutic treatment.